Strategi Komunikasi Persuasif Untuk Meningkatkan Brand Image Media Sosial Studi Kasus: Instagram @Adheliamakeup - Luthfiyah, Syaripah; Sari, Eka Anisa (Syntax Literate, 2025)
This study aims to analyze and describe the persuasive communication strategies employed by @adheliamakeup in building brand image through Instagram. The research focuses on analyzing the verbal and visual language used in content, the interaction style established through comment sections and direct messages (DMs), and the consistency of visual narratives presented through feeds, stories, and reels. Identifying the dominant elements of persuasive communication used in @adheliamakeup's Instagram content and evaluating the effectiveness of @adheliamakeup's persuasive communication strategies in enhancing brand image among the target audience. The approach used in this study is a descriptive qualitative method, with data collection techniques including observation, interviews, and documentation. Analysis is conducted using the Elaboration Likelihood Model (ELM) theory, which divides persuasive communication into two pathways: central and peripheral. The results of the study show that @adheliamakeup utilizes the peripheral pathway through the visual aesthetics of its posts, such as optimal lighting, color composition, and feed design consistency, which are able to attract the audience's attention emotionally. Meanwhile, the central pathway is realized through informative captions, customer testimonials, and two-way communication built through the comments section and direct messages (DM). Customer engagement strategies through reposting testimonials and sustained interaction are key factors in strengthening trust and fostering loyalty. The account's professional image is further reinforced by utilizing the highlight feature, which showcases service portfolios, customer reviews, and ordering information. With an engagement rate of 7–9%, this communication strategy is deemed successful in creating positive perceptions, increasing interaction, and building emotional connections between the brand and consumers.The research employed a descriptive qualitative approach with data collected via observation, interviews, and documentation. The analysis is based on the Elaboration Likelihood Model (ELM), which categorizes persuasive communication into two routes: central and peripheral. The findings reveal that @adheliamakeup leverages the peripheral route through visual aesthetics, including optimal lighting, harmonious color composition, and consistent feed layout, which effectively attract emotional responses from audiences. Meanwhile, the central route is demonstrated through informative captions, customer testimonials, and two-way communication facilitated by comments and direct messages (DMs). Customer involvement through reposted content and ongoing engagement plays a key role in building trust and fostering loyalty. The professional image of the brand is further reinforced by utilizing Instagram highlight features that showcase service portfolios, customer reviews, and booking information. With an engagement rate of 7–9%, the communication strategy successfully fosters positive perception, increases user interaction, and strengthens emotional bonds between the brand and its audience.